Evaluation of Adblock Software Usage - Sołtysik-Piorunkiewicz, Anna; Strzelecki, Artur; Abramek, Edyta (Complex Systems Informatics and Modeling Quarterly, 2019)
The article shows the main factors of adblocking software usage. The study was based on data obtained by a web questionnaire. The research was focused on evaluation of adblocking software usage factors in five categories: (1) gender, age, and education; (2) use of advertising and sources of knowledge about advertising; (3) technical and social reasons for blocking online advertisements; (4) usage of an adblock-wall; and (5) type of online advertisement. An evaluation of adblock usage factors revealed four main technical reasons for adblock usage connected with website technology and web development problems – interruption, amount of ads, speed, and security; and one social reason for adblock usage, namely, the problem of privacy.